RANCANG BANGUN SISTEM MONITORING DOCUMENT MANAGEMENT SYTEM PADA KANTOR NOTARIS – PPAT KUSDWIONO HARDIAN SANTOSO, S.H., M.KN DENGAN METODE BEST FIRST SEARCH - Muhammad Noval Riswandha; Mei Andayani (STMIK YADIKA BANGIL, 2021)
Abstract: The Notary Office – PPAT Kusdwiono Hardian Santoso, SH., M.Kn which is located at Jalan Salak Number 412, Bangil District, Pasuruan Regency is one of several Notaries who work in Pasuruan Regency, Notary - PPAT projects to make authentic deeds such as underhand agreements, sale and purchase agreement, making PT deed and many more. This Notary Office – PPAT handles various kinds of legal processes and keeps many important and confidential documents. In this study, the problems faced by Notaries or staff are management, document recording, and also searching for documents that have been made for a long time, the purpose of this research is to assist Notaries and staff in managing, recording and searching for documents using a monitoring system. With this monitoring system, it is hoped that it can assist Notaries and staff in monitoring existing documents, and also make it easier to search for documents. Keywords: Notary Office - PPAT, Monitoring System, Notary Pasuruan Regency.